PATHS TO INCREASE THE EFFICIENCY OF CLEANING THE SAW GIN (International Educators Conference, 2025)
The disadvantage of existing saw gins is their low cleaning efficiency. A new saw gin scheme has been developed, containing a front apron with a comb, a grate with a frontal beam, a saw cylinder and an air chamber with a nozzle, characterized in that the saw cylinder, in the direction of its rotation, is behind the grate, after the saws exit the gaps between the grates , a tuning shaft is installed, in which every two pegs adjacent along its length are located in such a way that the gap between them is located opposite each saw blade of the saw cylinder. This increases the efficiency of fiber cleaning.